Internships, Employability and the Search for Decent Work Experience - Andrew Stewart; Rosemary Owens; Shane Niall O'Higgins; Anne Hewitt (Edward Elgar Publishing, 2021)
This groundbreaking book examines the growing phenomenon of internships and the policy issues they raise, during a time when internships or traineeships have become an important way of transitioning from education into paid work.
Keywords: 330; internships; traineeships; education to work transitions; employability; active labour market policies; work-based learning; labour regulation; employment status; Praktikum; Arbeitsmarktpolitik; Arbeitsmarktintegration; Junge Arbeitskräfte; Beschäftigungssystem; Welt